Liquid exfoliation of defect-free graphene - COLEMAN, JONATHAN NESBIT (My University, 2013)
Due to its unprecedented physical properties, graphene has generated huge interest over the last 7 years. Graphene is generally fabricated in one of two ways: as very high quality sheets produced in limited quantities by micromechanical cleavage or vapour growth, or a rather defective, graphene-like material, graphene oxide, produced in large quantities. However, a growing number of applications would profit from the availability of a method to produce high quality graphene in large quantities.
PUBLISHED
Keywords: graphene